The Impact of Dedicated Education Model on Nursing Students' Outcomes: An Integrative Review. Issue 5 (4th September 2021) - Musallam, Eyad; Ali, Abeer Alhaj; Nicely, Stephanie
Abstract : Supplemental digital content is available in the text. Abstract : Background: Dedicated education units (DEUs) provide an approach to clinical redesign in nursing education. However, the evidence supporting the application of the DEU model has not been systematically reviewed to assess the impact of this model on students' learning outcomes. Purpose: This integrative review analyzed the evidence on the relationship between the DEU model and nursing students' learning outcomes. Methods: Electronic databases were searched for articles published between 1998 and 2019. Search terms used were dedicated education unit, academic collaboration, academic-practice partnership, and outcomes . A total of 24 articles informed this review. Results: Four categories emerged: clinical self-efficacy and confidence, teamwork and collaboration, knowledge and competency, and students' satisfaction. Conclusion: The main findings support a positive relationship between the DEU model and students' learning outcomes. Research is still needed to investigate the impact of DEU models on students' problem-solving and clinical judgment.